THE RIVER BASIN APPROACH IN TOURISM PLANNING - Agita Slara (European Regional Science Association (ERSA), 2005)
The article describes advantages and disadvantages in tourism planning, using the river basins as background territory and borders. Tourism development planning is taking place according administrative territorial borders till nowadays in Latvia and in other tourism destinations in abroad. According tourist and visitor needs and environmental friendly approach it is more appropriate to use river basins in tourism planning. Tourists are not interested in administrative borders, but in qualitative tourism products and services. Tourism industry is integrated sector including: traffic, communication, accommodation, energy, public catering, attractions, travel and destination organizers and institutional support to industry. Tourism planning in administrative borders supports fractioned human, nature and financial resources, which finally gives weak and unpopular tourism products. The author has selected as case study for tourism planning Daugava river basin, exactly Ogre – Daugava's right side tributary - basin. Daugava river basin is in 15th place in ecoregion "Baltic Province” and in 5th place in ecoregion "Baltic Sea” according Water structure directive EEC 2000/60/EC; 11 annex. In year 2003 there is finished project "Daugava basin area management plan” which focuses on planning issues according river basins (Daugava project Latvia Sweden, 2003). The author has selected tributary Ogre basin (area 1730km2), it is 3rd largest river in Latvia (188km) and one of the most attractive rivers for water tourists. It is crucial to develop and strengthen tourism services along the Ogre river, if local enterprises want to receive profit from water tourism. One legal accommodation and two places for tents are situated in Ogre riverbanks. In the course of tourism planning at least primary problems must be solved: lack of toilets, collection of waste, types of water transport. The article prepared using practical observation of the Ogre river basin, interviews with local enterprisers and water tourists in the area. The main conclusions are lack of understanding role of river basin in sustainable way and administrative obstacles for common cooperation. Tourism planning according river basins approach gives preconditions for elaboration sustainable tourism development services and tourism products.
Keywords: 330